2007
DOI: 10.1097/bpo.0b013e3181558856
|View full text |Cite
|
Sign up to set email alerts
|

All-Terrain Vehicle Injuries in Children

Abstract: Orthopaedic injuries are the norm in children and adolescents injured in ATV accidents. Although some legislation is in place, the level of compliance is unclear. Legislation requiring helmet use and age limits failed in Oklahoma this year. Perhaps a comprehensive community education program would be the most effective in decreasing ATV morbidity and mortality in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Extremity injuries were the most common injuries in the study, a common finding in all studies on paediatric motorcycle and ATV use 9 . Orthopaedic procedures were therefore the most common operations performed on patients in the study period.…”
Section: Discussionmentioning
confidence: 84%
“…Extremity injuries were the most common injuries in the study, a common finding in all studies on paediatric motorcycle and ATV use 9 . Orthopaedic procedures were therefore the most common operations performed on patients in the study period.…”
Section: Discussionmentioning
confidence: 84%
“…13,14 Furthermore, the NEISS has served a reliable and reproducible source for a wide range of epidemiological subjects that present to the emergency department for medical care. [15][16][17][18][19][20][21] Statistical Analysis…”
Section: Methodsmentioning
confidence: 99%
“…14 Notably children involved in ATVC sustain injuries from every body system, implore high risk riding practices, and demonstrate a high rate of recidivism. [14][15][16][17][18] Due to their vulnerability, some reports suggest minors less than 11 years old should not be allowed to ride ATVs. 19 Our study found a significantly increased incidence of ATVC in children less than 16 years old compared with those involved in MCC.…”
Section: Discussionmentioning
confidence: 99%